The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jbmr.3658
|View full text |Cite
|
Sign up to set email alerts
|

Possible Contribution of Wnt-Responsive Chondroprogenitors to the Postnatal Murine Growth Plate

Abstract: Active cell proliferation and turnover in the growth plate is essential for embryonic and postnatal bone growth. We performed a lineage tracing of Wnt/β‐catenin signaling responsive cells (Wnt‐responsive cells) using Axin2CreERT2;Rosa26ZsGreen mice and found a novel cell population that resides in the outermost layer of the growth plate facing the Ranvier's groove (RG; the perichondrium adjacent to growth plate). These Wnt‐responsive cells rapidly expanded and contributed to formation of the outer growth plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…For example, Prg4-creERT2 labels the progenitors of the superficial zone of the articular cartilage, 127 PTHrP-creERT2 labels the progenitors in the reserve zone of the growth plate, 128 and Axin2-creERT2 labels the progenitors in and around the groove of Ranvier. 129 In studies on IVD, lineage tracing experiments by Choi et al employing Shh-cre and Shh-creERT2 alleles showed that the notochord is the sole source of cells that form the entire NP. 130 This was further confirmed by the lineage tracing experiments using the Noto-cre allele.…”
Section: Ivd Specific Progenitors In Vitromentioning
confidence: 99%
“…For example, Prg4-creERT2 labels the progenitors of the superficial zone of the articular cartilage, 127 PTHrP-creERT2 labels the progenitors in the reserve zone of the growth plate, 128 and Axin2-creERT2 labels the progenitors in and around the groove of Ranvier. 129 In studies on IVD, lineage tracing experiments by Choi et al employing Shh-cre and Shh-creERT2 alleles showed that the notochord is the sole source of cells that form the entire NP. 130 This was further confirmed by the lineage tracing experiments using the Noto-cre allele.…”
Section: Ivd Specific Progenitors In Vitromentioning
confidence: 99%
“…In vitro these ep-SSPCs can directly differentiate into osteoblasts, chondrocytes and, to a lesser extent, adipocytes ( Mizuhashi et al, 2018 ); whereas in vivo they generate chondrocytes, which then undergo hypertrophy and transdifferentiate into osteoblasts and stromal cells ( Mizuhashi et al, 2018 ). During the juvenile period of growth, additional ep-SSPCs probably move from the perichondrium into the periphery of the resting zone, as revealed by genetic tracing of Axin2-positive perichondrial cells ( Usami et al, 2019 ).…”
Section: The Stem Cell Niche In the Epiphyseal Growth Platementioning
confidence: 99%
“…Thus, Hh activity, and in particular Gli1 expression, may generally mark stem cells within a range of skeletal tissues, including the developing perichondrium, the growth plate, the metaphysis bone marrow compartment, and the periosteum. This broad contribution is similarly observed using Axin2-CreER, suggesting that SSCs may also be Wnt responsive, though it is unclear whether these two transgenes mark the same populations (Maruyama et al, 2016;Ransom et al, 2016;Usami et al, 2019).…”
Section: Box 2 Endochondral Versus Direct Ossificationmentioning
confidence: 69%